Association between red blood cell distribution width and genetic risk in patients with rheumatoid arthritis: a prospective cohort study and Mendelian randomization analysis - Mingyang Chen; Jing Lei; Zhenqiu Liu; Renjia Zhao; Yanfeng Jiang; Kelin Xu; Tiejun Zhang; Chen Suo; Xingdong Chen (BMC Rheumatology)
Abstract Objective Elevated red blood cell distribution width (RDW) is associated with increased risk of rheumatoid arthritis (RA), but the potential interactions of RDW with genetic risk of incident RA remain unclear. This study aimed to investigate the associations between RDW, genetics, and the risk of developing RA. Methods We analysed data from 145,025 healthy participants at baseline in the UK Biobank. The endpoint was diagnosed rheumatoid arthritis (ICD-10 codes M05 and M06). Using previously reported results, we constructed a polygenic risk score for RA to evaluate the joint effects of RDW and RA-related genetic risk. Two-sample mendelian randomization and bayesian colocalization were used to infer the causal relation between them. Results A total of 675 patients with RA were enrolled and had a median followed up of 5.1 years, with an incidence rate of 0.57/1000 person-years. The hazard ratio of RA was 1.89 (95% CI: 1.45, 2.47) in highest RDW quartile group compared with the lowest RDW quartile group. Individuals within the top quintile of PRS showed a significantly high risk of RA. Moreover, Participants with high genetic risk and those in highest RDW group exhibited a significantly elevated hazard ratio (7.67, 95% CI: 3.98, 14.81), as opposed to participants with low genetic risk and those in lowest RDW group. Interactions between PRS and RDW on the multiplicative and additive scale were observed. Mendelian randomization provided suggestive evidence of a bi-directional causal relationship between RDW and RA. Loci near IL6R, IL1RN, FADS1/FADS2, UBE2L3 and HELZ2 showed colocalization. Conclusion Increased RDW is associated with elevated risk of incident RA especially in the high genetic risk populations, but only suggestive evidence supports a causal relationship between them.